THE USE OF PERSONAL VOCABULARY NOTES (PVN) TO INCREASE STUDENTS’ VOCABULARY MASTERY at SMP NEGERI 2 SONDER - Montolalu, Carla Firamita; Mogea, Tini; Ceisy N. Wuntu (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This research aims to find out whether personal vocabulary notes can increase students’ vocabulary mastery at SMP Negeri 2 Sonder and the sample of this study is students grade 8 which consist of 12 students. This research is quantitative research used pre-experimental design with one-group pre-test and post-test. The researcher collects the data from pre-test or before giving treatment and post-test after giving treatment. Based on findings, it shows that before being given treatment, students got grades that were not good enough on the pre-test but on post-test, or after being given treatment, the grades obtained by students exceeded the pre-test and with quite a significant difference. The result of mean score on pre-test was 47 and on the post-test it was 77,08 it means that the post test score was higher than the pre-test. For the significance level (P= 0.05) and df = 11, and it is known that the value of the t test is 25.70 and the value of the t table is 2.201, it can be seen that the value of the t test is greater than the t table or t test ≥ t table (25.70 ≥ 2.201). From the data, it can be concluded that Personal Vocabulary Notes (PVN) can increase students’ vocabulary mastery.